2005
DOI: 10.1063/1.2037567
|View full text |Cite
|
Sign up to set email alerts
|

Second order superintegrable systems in conformally flat spaces. III. Three-dimensional classical structure theory

Abstract: This paper is part of a series that lays the groundwork for a structure and classification theory of second-order superintegrable systems, both classical and quantum, in real or complex conformally flat spaces. Here we consider classical superintegrable systems with nondegenerate potentials in three dimensions. We show that there exists a standard structure for such systems, based on the algebra of 3 ϫ 3 symmetric matrices, and that the quadratic algebra always closes at order 6. We show that the spaces of tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(135 citation statements)
references
References 31 publications
0
133
0
2
Order By: Relevance
“…[5][6][7] Like much of the later work on superintegrable systems, it was restricted to the case of second-order integrals of motion. [8][9][10][11][12][13] This case turned out to have an intimate connection with the separation of variables in the HamiltonJacobi and Schrödinger equations.…”
Section: ͑14͒mentioning
confidence: 99%
“…[5][6][7] Like much of the later work on superintegrable systems, it was restricted to the case of second-order integrals of motion. [8][9][10][11][12][13] This case turned out to have an intimate connection with the separation of variables in the HamiltonJacobi and Schrödinger equations.…”
Section: ͑14͒mentioning
confidence: 99%
“…However, in the 3D case there are only 5 functionally independent symmetries, so we can't guarantee that the symmetry equations admit a 6-parameter family of solutions. Fortunately, by careful study of the integrability conditions of these equations and use of the requirement that the potential is nondegenerate, we can prove the 5 =⇒ 6 theorem [20].…”
Section: The 5 =⇒ 6 Theoremmentioning
confidence: 99%
“…This means that we require that the five quadratic forms L h , H 0 are functionally independent.) In [20] it is shown that the matrix of the 15 Bertrand-Darboux equations for the potential has rank at least 5, hence we can solve for the second derivatives of the potential in the form…”
Section: Conformally Flat Spaces In Three Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations